Pest outbreaks in tropical forest plantations: is there a greater risk for exotic tree species? - Nair, K.S.S. (Center for International Forestry Research, 2001)
In the context of the ongoing expansion of forest plantations of exotic tree species in the tropics, a critical assessment was made of the risk of insect pest outbreaks in exotics. To date, there have been two opposing views: that plantations of exotic species are at greater risk compared to indigenous species and conversely, that exotics are at lesser risk. Both views rest on theoretical arguments. In this study, an empirical approach was used to address the issue. For nine most commonly planted species in the tropics, the pest problems in natural forest stands, in countries in which the species are indigenous (native plantations), and in exotic plantations were compared. The species chosen were Acacia mangium, Eucalyptus spp., Gmelina arborea, Hevea brasiliensis, Leucaena leucocephala, Paraserianthes falcataria, Pinus caribaea, Swietenia macrophylla and Tectona grandis. The results showed that: (1) monoculture itself caused an increase in the pest problems; and (2) the pest risk of exotics was variable, for some species similar to that of native plantations, while greater or lesser for others. The risk of pest outbreak is therefore not solely dependent on the exotic or indigenous status of a species. Empirical results also showed that pest outbreaks occurred in native plantations. The theory relating to insect population dynamics and causes of pest outbreaks is discussed and based on a mix of empirical evidence and theory. It is concluded that the following factors determine the risk of pest outbreak in exotic monoculture plantations: (1) presence or absence of plant species closely related to the exotic; (2) extent of area under the exotic species; (3) genetic base of the planted stock; (4) distance from the native habitat of the exotic; (5) existence of serious pests in the native habitat of the exotic; (6) time elapsed since introduction; (7) chemical profile of the exotic species; and (8) innate biological attributes of the insects associated with a tree species. The overall conclusion from this study is that while all monoculture plantations are at greater risk of pest outbreaks than natural forests, plantations of exotics are at no greater risk than plantations of indigenous species. It should be possible to develop a pest risk rating system for different tree species for different locations, based on these criteria.